2008
DOI: 10.1016/j.biomaterials.2008.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-targeted siRNA delivery by prostaglandin E2-Fas siRNA polyplexes formulated with reducible poly(amido amine) for preventing cardiomyocyte apoptosis

Abstract: A cardiomyocyte-targeted Fas siRNA delivery system was developed using prostaglandin E 2 (PGE 2 )-modified siRNA polyplexes formed by a reducible poly(amido amine) to inhibit cardiomyocyte apoptosis. PGE 2 , which was used as a specific ligand for cardiomyocyte targeting, was conjugated to the terminal-end of the sense siRNA (PGE 2 -siRNA). The reducible cationic copolymer, synthesized via Michael-type polyaddition of 1,6-diaminohexane and cystamine bisacrylamide (poly(DAH/CBA)), tightly condensed the PGE 2 -s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…To overcome these hurdles, delivery of siRNA with polymeric carriers has been proposed as an attractive solution. In our previous studies, we have reported the cardiomyocyte-targeting bioreducible polymer for siRNA delivery to the myocardium [6063]. …”
Section: Disease Applications Of Bioreducible Polymersmentioning
confidence: 99%
“…To overcome these hurdles, delivery of siRNA with polymeric carriers has been proposed as an attractive solution. In our previous studies, we have reported the cardiomyocyte-targeting bioreducible polymer for siRNA delivery to the myocardium [6063]. …”
Section: Disease Applications Of Bioreducible Polymersmentioning
confidence: 99%
“…A linear SS-PAA, synthesized by copolymerization between 1,6-diaminohexane and cystamine bis-acrylamide (cystamine bisacrylamide-diamino hexane (poly(DAH/CBA)), served as a powerful vector to carry Fas siRNA into rat cardiomyocytes [104]. PGE2 was conjugated to Fas siRNA molecules, and the synthesized PGE2–Fas siRNA contributed to cardiomyocyte targeting via PGE2 receptor-mediated intracellular delivery.…”
Section: Targeted Gene Delivery Into Myocardiummentioning
confidence: 99%
“…1): (a) formation of compact nano-scale complexes between nucleic acid drug and carrier compounds, (b) choice of a route of administration, (c) systemic circulation, (d) target tissue localization, (e) intracellular transport, (f) escape from endocytic compartments such as endosomes and lysosomes, (g) nuclear transport, and (h) gene expression (6). Unlike plasmid DNA for gene expression, siRNA needs to rapidly escape from the intracellular organelles into the cytoplasm without being localized to the nucleus, where siRNA induces RNAi (7). Although a number of previously developed gene carriers have been used for siRNA, RNAi-based approaches for clinical therapy require more carefully designed delivery systems to achieve the maximum gene silencing effect.…”
Section: Introductionmentioning
confidence: 99%